Smart Transport Performance in Sweden’s Urban Context - Björn, Kokaia; Larsson, Schmid; Nilsson, Bergquist (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Urban transport faces rising challenges of congestion, energy inefficiency, and emissions. Sweden has pioneered smart mobility innovations, including electric roads (e-roads), electrified public buses, and integrated intelligent transport systems (ITS). This article provides a technical analysis of Sweden’s smart transport infrastructure, focusing on the design of e-roads, autonomous vehicle trials, and digital mobility platforms. Using secondary data from government reports, scientific studies, and engineering case documentation, the study examines system architecture, energy efficiency, and operational scalability. The findings highlight Sweden’s successful integration of electrification, real-time data systems, and multimodal connectivity. Technical limitations such as infrastructure costs, interoperability, and cybersecurity are also identified. The paper concludes that Sweden’s applied smart transport technologies can serve as a blueprint for other urban contexts, particularly in developing cities seeking to transition toward sustainable mobility.